1992
DOI: 10.1021/bi00141a008
|View full text |Cite
|
Sign up to set email alerts
|

Extensive comparison of the substrate preferences of two subtilisins as determined with peptide substrates which are based on the principle of intramolecular quenching

Abstract: Subtilisins are serine endopeptidases with an extended binding cleft comprising at least eight binding subsites. Interestingly, subsites distant from the scissile bond play a dominant role in determining the specificity of the enzymes. The development of internally quenched fluorogenic substrates, which allow polypeptides of more than 11 amino acids to be inserted between the donor and the acceptor, has rendered it possible to perform a highly systematic mapping of the individual subsites of the active sites o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(70 citation statements)
references
References 31 publications
2
68
0
Order By: Relevance
“…While the hydrophobic S I and S4 binding pockets appear to dominate substrate binding in subtilisins (Gron et al, 1992), our analysis of binding sites in NisP suggests that electrostatic interactions may alternatively contribute to binding and even dominate overall selectivity (or specificity). In particular, in the case of NisP and EpiP, one or more negative charges in the S I pocket can lead to a high selectivity for a basic PI residue in the substrate.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…While the hydrophobic S I and S4 binding pockets appear to dominate substrate binding in subtilisins (Gron et al, 1992), our analysis of binding sites in NisP suggests that electrostatic interactions may alternatively contribute to binding and even dominate overall selectivity (or specificity). In particular, in the case of NisP and EpiP, one or more negative charges in the S I pocket can lead to a high selectivity for a basic PI residue in the substrate.…”
Section: Discussionmentioning
confidence: 77%
“…The S4 pocket of NisP is predicted to be smaller than that of subtilisin due to several large predominantly hydrophobic side chains (Table II). While interaction of the small residue Ala(P4) of precursor nisin in this pocket may be less important than the S I-P I interaction, it was shown that Ala(P4) is not unfavourable for subtilisin and is still a good substrate even for the larger hydrophobic S4 pocket of subtilisin (Gron et al, 1992). The Ser(P3) of precursor nisin does not appear to interact directly with NisP, although hydrogen bonding to NI43 is possible.…”
Section: Substrate Bindingmentioning
confidence: 99%
See 1 more Smart Citation
“…The linkages between protein domains are often particularly susceptible to proteolysis. Subtilisin is known as a protease having a broad subsite specificity [36,37]. Therefore, it is comprehensible that proteins possibly are readily digested when employed in subtilisin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…G T ‡ (changes in transition state stabilization energy) of the peptides was calculated using the relative difference in k cat /K m values [28], where G T ‡ is negative if the X-X-X-Arg peptide is a better substrate than the Y-Y-Y-Arg peptide (where X and Y are any amino acid):…”
Section: Figure 1 Specificity Profile Of Rfviia In the Presence Of Stfmentioning
confidence: 99%